Pupil exchanges and their role in intercultural education - Jakosz, Mariusz (Glottodidactica, 2022)
Intercultural education is one of the most important goals of contemporary foreign language teaching. In order to keep pupils strongly motivated to learn foreign languages, they must be made to understand what benefits can be gained from a good command of foreign languages. It is due to international pupil exchanges that young people have the opportunity to come into direct contact with a foreign language, to experience foreign culture in real communicative situations, and in the process verify or overcome deeply rooted stereotypes and prejudices about certain nations. In the article, the author presents quantitative questionnaire results, which allows him to identify the heterostereotypes of Polish and German pupils as well as their attitude towards historical events and current bilateral relations. Additionally, the impact of pupil exchanges on how representatives of both nations see each other and on their further contacts has been discussed. The results obtained can serve not only as guidelines on how to work with stereotypes and prejudices in foreign language classes, but they might also help in effective preparation for the scheduled pupil exchange.